2019
DOI: 10.1051/0004-6361/201834374
|View full text |Cite
|
Sign up to set email alerts
|

Link between brightest cluster galaxy properties and large scale extensions of 38 DAFT/FADA and CLASH clusters in the redshift range 0.2 < z < 0.9

Abstract: Context. In the context of large-scale structure formation, clusters of galaxies are located at the nodes of the cosmic web, and continue to accrete galaxies and groups along filaments. In some cases, they show a very large extension and a preferential direction. Brightest cluster galaxies (BCGs) are believed to grow through the accretion of many small galaxies, and their structural properties are therefore expected to vary with redshift. In some cases BCGs show an orientation comparable to that of the cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 47 publications
(62 reference statements)
3
56
2
Order By: Relevance
“…Similarly, Cerulo et al (2019) did not find significant stellar mass growth between z = 0.35 and z = 0.05, suggesting that most of the BCGs stellar masses were formed by z = 0.35. Durret et al (2019) observed a possible variation with redshift of the effective radius of the outer Sérsic component of BCGs for 38 BCGs in the redshift range 0.2 ≤ z ≤ 0.9, agreeing with a scenario in which BCGs at these redshifts mostly grow by accreting smaller galaxies.…”
Section: Introductionsupporting
confidence: 80%
“…Similarly, Cerulo et al (2019) did not find significant stellar mass growth between z = 0.35 and z = 0.05, suggesting that most of the BCGs stellar masses were formed by z = 0.35. Durret et al (2019) observed a possible variation with redshift of the effective radius of the outer Sérsic component of BCGs for 38 BCGs in the redshift range 0.2 ≤ z ≤ 0.9, agreeing with a scenario in which BCGs at these redshifts mostly grow by accreting smaller galaxies.…”
Section: Introductionsupporting
confidence: 80%
“…The dark matter halo and the BCG are therefore thought to be aligned, as is indicated by simulations (e.g. Schneider et al 2012) and observations (Donahue et al 2016;Wittman et al 2019;Durret et al 2019). Even beyond the BCG, the distribution of the intracluster light has been shown to follow the distribution of dark matter closely (Montes & Trujillo 2019).…”
Section: Introductionmentioning
confidence: 77%
“…First, we looked at the histograms of all the redshifts available in a large zone around each cluster (for the DAFT/FADA clusters, these histograms were given by Guennou et al 2014 andDurret et al 2016); for the other clusters we retrieved all the redshifts available in NED and drew their histogram in the approximate cluster redshift range. We also looked at the matter distribution based on a weak lensing analysis by Martinet et al (2016) or on the shape of the red sequence density map by Durret et al (2016Durret et al ( , 2019. For clusters with at least 10 spectroscopic redshifts available within the HST images analysed in the present paper, we looked at the proportion of jellyfish galaxy candidates relative to the relaxation state of the cluster.…”
Section: Discussionmentioning
confidence: 99%
“…For each cluster, we identify galaxies with spectroscopic redshifts in the range previously chosen to draw galaxy density maps (Durret et al 2016(Durret et al , 2019 and roughly corresponding to an interval of ±0.02 around the corresponding cluster redshift. This translates into a velocity range indicated in Table 1 for each cluster, expressed in units of the corresponding cluster velocity dispersion (computed in Sect.…”
Section: Selection Of Jellyfish Candidatesmentioning
confidence: 99%
See 1 more Smart Citation